An application of Altman's Z-score on selected manufacturing companies in the Philippines covering the period of 1978-1998 - Astom, Nikki Anne F. (Animo Repository, 1999)
Executive Summary. Ratio analysis is a basic and powerful indicator of a firm's financial performance. From selected ratios derived from a Multivariate Discriminant Analysis, Edward I. Altman (1968) came up with a prediction model of bankruptcy using data of manufacturing companies in the United States. In the study, a combination of various financial ratios was utilized simultaneously. The result is the Z-score which can discriminate between bankrupt and non-bankrupt companies. The purpose of this paper is to test and validate Edward I. Altman's model on its adaptability on Philippine manufacturing companies. This paper aims to determine the accuracy of the Z-score and its predictive capacity when applied to Philippine Manufacturing Companies. The study can be significant to managers, analysts, owners, shareholders and creditors for business credit evaluation, internal control considerations and investment policies. The data used in the study are limited to privately owned manufacturing companies in the Philippines. The sample is composed of fifty manufacturing corporations with twenty-five firms in each of the two groups, the bankrupt group (Group I) and the non-bankrupt group (Group 2). Audited Financial Statements has been the secondary source of data analysis. Bankrupt firms and non-bankrupt firms are matched and F-test was employed in order to test the individual discriminating ability of the variables and to prove that the sample means of each group are significantly different, which shows that they came from a heterogeneous population. The scaled vector determines which of the five variables contributed the most to the discriminating power of the function. With a 92% accuracy one year prior to bankruptcy and 76% accuracy two years prior to bankruptcy, the study has shown conclusive evidence that the model of E. Altman has been validated here in the Philippine setting using selected manufacturing companies. Together with this, a lead time was ascertained which is 22.4 months prior to bankruptcy of the investigated firms under review. The financial ratios have its limitations but when strategically used can be predictive of the firm's likelihood of bankruptcy. The proponents do not claim that the sample is statistically valid to represent the whole Philippine Manufacturing Industry but it has been proven that the model can apply for these selected companies. Further research using a larger sample over a longer period of time is recommended.